Fallout - Strasser, Todd (Candlewick Press, 2015)
In 1962 nuclear war begins and Scott's family races to their bomb shelter--the only one in town. Others fight to get in, and eventually ten people cram in the small space with scarce supplies hoping to survive the unthinkable.